Electoral outcomes, power outages and firm performance - DENİZ, PINAR (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
Even though a wide range of the literature explores how governments target public goods strategically, only a handful of papers examine whether these electorally motivated distributive patterns have consequences for the real economy. With the use of Turkish electoral and firm-level data, this paper examines whether electoral factors affect the variation in power outages experienced by firms across Turkish regions. The findings demonstrate that sales of firms located in regions in which the incumbent party received more votes were disproportionately higher because these firms experienced relatively lower numbers and durations of power outages.
Keywords: distributive politics; power outages; firm performance; regional inequality; ECONOMIC-GROWTH EVIDENCE; DISTRIBUTIVE POLITICS; ELECTRICITY SHORTAGES; ALLOCATION; PARTIES; VOTE; DETERMINANTS; CONNECTIONS; INVESTMENT; IDEOLOGY